PEMANFAATAN STRATEGIS TIKTOK SEBAGAI MEDIA PROMOSI PRODUK DI KALANGAN UMKM MILENIAL: SEBUAH PERSPEKTIF ANALITIS - Andi Alfianto Anugrah Ilahi; Arifuddin Arifuddin; Darmawansah Darmawansah (Management Studies and Business Journal (PRODUCTIVITY), 2026)
This study aims to explore the utilization of TikTok as a product promotion medium by Micro, Small, and Medium Enterprises (MSMEs) owned by millennials. In today’s rapidly evolving digital era, TikTok has become one of the most popular and potential social media platforms for reaching consumers broadly and quickly. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with five millennial MSME actors who actively use TikTok to market their products. The findings reveal that TikTok is perceived as an effective platform for building brand awareness, creating audience engagement, and significantly increasing sales. MSME actors also take advantage of creative features such as music, filters, and hashtag challenges to attract consumer attention. Nevertheless, challenges such as algorithm changes, limited technical knowledge, and the need for consistent content remain obstacles to optimizing TikTok utilization. This study provides new insights into relevant digital promotion strategies for MSMEs in the era of social media, particularly through creative approaches favored by the millennial generation.